2020
DOI: 10.13181/mji.oa.203633
|View full text |Cite
|
Sign up to set email alerts
|

MLH1 and MSH2 mismatch repair protein profile using immunohistochemistry in Nepalese colorectal cancer patients

Abstract: BACKGROUND Hereditary nonpolyposis colorectal cancer, or Lynch syndrome, caused by germline mutations or genetic defects in mismatch repair (MMR) genes (MLH1, MSH2, PMS2, MSH6, and epithelial cellular adhesion molecule), is an autosomal dominant condition accounting for 2–5% of all colorectal carcinomas (CRCs). Reports on MMR loss in many populations are available; however, there are no reports on the frequency of MMR protein expression in Nepalese cohorts. Therefore, this study was aimed to assess the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Several polymorphism studies have shown the strong association of SNPs toward the susceptibility of cancer. 9,10 Elek et al 11 have recently demonstrated that SNP rs34944508 influences MGAT5 expression, which catalyzes the addition of Nacetylglucosamine (GlcNAc) in β [1][2][3][4][5][6] linkage to mannose of N-linked oligosaccharide, which is a characteristic of invasive lung malignancies. A study conducted by Slovakova et al 12 on promoter polymorphisms for selected MMR genes viz MSH2 (rs2303425) has evaluated the risk of cancer development in both dominant and recessive genetic models and demonstrated that polymorphism of MMR genes MSH2 is associated with a risk of developing sporadic cancer and hereditary tumors in Slovak people.…”
Section: F I G U R E 1 Location Of Different Domains On Msh2 Proteinmentioning
confidence: 99%
See 2 more Smart Citations
“…Several polymorphism studies have shown the strong association of SNPs toward the susceptibility of cancer. 9,10 Elek et al 11 have recently demonstrated that SNP rs34944508 influences MGAT5 expression, which catalyzes the addition of Nacetylglucosamine (GlcNAc) in β [1][2][3][4][5][6] linkage to mannose of N-linked oligosaccharide, which is a characteristic of invasive lung malignancies. A study conducted by Slovakova et al 12 on promoter polymorphisms for selected MMR genes viz MSH2 (rs2303425) has evaluated the risk of cancer development in both dominant and recessive genetic models and demonstrated that polymorphism of MMR genes MSH2 is associated with a risk of developing sporadic cancer and hereditary tumors in Slovak people.…”
Section: F I G U R E 1 Location Of Different Domains On Msh2 Proteinmentioning
confidence: 99%
“…MutS Homolog 2 (MSH2) protein plays an essential role in DNA repair and is associated with different cancer such as hereditary nonpolyposis colorectal cancer (HNPCC), Lynch syndrome, and lung cancer 1–3 . MSH2 comprises two interaction domains (MSH3/MSH6 and MSH2/PMS2) and one DNA binding domain, which are present in two different locations on the gene (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation